SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KEPALA LABORATORIUM DENGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) DI RUMAH SAKIT GRANMED - Vera Mayora Br. Ginting; Fricles Ariwisanto Sianturi (Journal Of Informatic Pelita Nusantara, 2019)
Grandmed hospital is private hospital which is located at the bottom of Lubuk Pakam, Deli Serdang regency. Since 09 December 2009 Grandmed hospital officially operates under the auspices of the Medistra Foundation also has a ursing academy, midwifery academy, health institute Medistra. Grandmed hospital have many installations on of which is a laboratory. Making a decision support system for laboratory head election is needed by Grandmed hospital. This system will facilitate the selection of laboratory head and this system will also help evaluate the performance of laboratory staff. Therefore, decision support system using methods Simple Additive Weighting (SAW) suitable for this system, this system will facilitate the search, and speed up the valuation calculation, and attribute to determine laboratory employees who deserve to be heads. Simple Additive Weighting method can be used as  a method in making applications in decision making. Simple additive wieghting uses the value sequencing system to determine the attribute rating, where the rating of each attribute is summed wiith the weight of the attribute in question. Simple additive wieghting method is often also known as the weighted addition method. The basic concept  of the Simple additive wieghting method is to find the weighted sum of  performance  rating for each alternative  in each attribute. The Simple additive wieghting method is recommended to solve the selection problem in a multi-process decision making system.